In vitro profiling of toxicity and endocrine disrupting effects of bisphenol analogues by employing MCF‐7 cells and two‐hybrid yeast bioassay. Issue 1 (24th February 2016) - Lei, Bingli; Xu, Jie; Peng, Wei; Wen, Yu; Zeng, Xiangying; Yu, Zhiqiang; Wang, Yipei; Chen, Tian
ABSTRACT: The potentially adverse health implications of bisphenol A (BPA) have led to increasing use of alternative bisphenols (BPs). However, little is known about the toxicity of alternative BPs. In this study, the cytotoxicity, genotoxicity, intracellular ROS formation, and Ca 2+ fluctuation effects of BPs on MCF‐7 cells were evaluated. At the same time, the estrogenic and thyroidal hormone effect potentials of six BPs were also evaluated using two‐hybrid yeast bioassay. The results showed that most BPs at 0.01–1 μM significantly increased cell viability in MCF‐7 cells and at higher exposure concentrations of 25–100 μM, they caused a significant decrease of cell viability. At the same time, these BPs also at 25–100 μM significantly increased LDH release of MCF‐7 cells. In addition, several BPs at 10–50 μM resulted in a significantly concentration‐depended increase in DNA‐damaging effect on MCF‐7 cells and elevated ROS production. Most BPs at 0.0001–10 μM significantly increased intracellular Ca 2+ level. These results showed that bisphenol AF (BPAF) and thiodiphenol (TDP) exerted cell biological effect, estrogenic, and thyroidal effect potentials greater than those of BPA. The cytotoxicity and endocrine disrupting effects of other BPs are similar to or slightly lower than those of BPA. Therefore, as potential alternatives to BPA, endocrine disrupting effects and potential health harm of alternative BPs to human can also not be ignored. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 278–289, 2017.